2017
DOI: 10.1074/jbc.m116.760322
|View full text |Cite
|
Sign up to set email alerts
|

Human Keratinocytes Respond to Extracellular UTP by Induction of Hyaluronan Synthase 2 Expression and Increased Hyaluronan Synthesis

Abstract: The release of nucleotides into extracellular space is triggered by insults like wounding and ultraviolet radiation, resulting in stimulatory or inhibitory signals via plasma membrane nucleotide receptors. As similar insults are known to activate hyaluronan synthesis we explored the possibility that extracellular UTP or its breakdown products UDP and UMP act as mediators for hyaluronan synthase () activation in human epidermal keratinocytes. UTP increased hyaluronan both in the pericellular matrix and in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 96 publications
2
14
0
Order By: Relevance
“…Unexpectedly, HAS-deficient mice did not display any significant differences in tendon HA contents or HAS expression compared to WT mice, at any age. Since HAS2 appears to be the predominant isoform for synthesis of high molecular weight HA in connective tissues, 44 its low expression in all genotypes (WT and HAS-deficient) combined with no detectable change in the total HA concentration or stainable HA of the tendon, is consistent with the findings on post-translational control of HAS2 via protein glycosylation 45 and UDP precursor supply. 46 Therefore, to further our understanding of the function of HA metabolism in tendon cell proliferation and differentiation, and in ECM organization, the regulation of HAS2 catalytic activity 45,[47][48][49] and the auxillary roles of HAS1 and HAS3 proteins 50 should be explored.…”
Section: Discussionsupporting
confidence: 86%
“…Unexpectedly, HAS-deficient mice did not display any significant differences in tendon HA contents or HAS expression compared to WT mice, at any age. Since HAS2 appears to be the predominant isoform for synthesis of high molecular weight HA in connective tissues, 44 its low expression in all genotypes (WT and HAS-deficient) combined with no detectable change in the total HA concentration or stainable HA of the tendon, is consistent with the findings on post-translational control of HAS2 via protein glycosylation 45 and UDP precursor supply. 46 Therefore, to further our understanding of the function of HA metabolism in tendon cell proliferation and differentiation, and in ECM organization, the regulation of HAS2 catalytic activity 45,[47][48][49] and the auxillary roles of HAS1 and HAS3 proteins 50 should be explored.…”
Section: Discussionsupporting
confidence: 86%
“…UTP increases the phosphorylation of p38, ERK, and Ser-727 of STAT3 in human keratinocytes. p38, ERK, and STAT3 inhibitors partially block the activation of HAS2 expression which confirms the involvement of these pathways in the UTP-induced HAS2 response [42]. In this study, we found that PFKFB4 induces p38 and ERK phosphorylation, but not STAT3 or Akt phosphorylation.…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 66%
“…As extracellular nucleotides are similarly released after tissue injury, it is relevant to ask, whether these processes could be linked. Previous data on the effects of nucleosides and nucleotides on hyaluronan metabolism are scarce, but adenosine is known to upregulate HAS1 expression and hyaluronan secretion in gingival fibroblasts [36] and smooth muscle cells [37], while UDP-Glc, UTP and UDP enhance HAS2 expression and hyaluronan synthesis in keratinocytes [38,39].…”
Section: Hyaluronan Is Composed Of Repeating Disaccharides Of D-glucumentioning
confidence: 99%
“…Intriguingly, if the expression of A 2A dominates, which can occur in stressed tissues [77] or malignancies [78], activation of p38 signaling could increase the expression of HAS2, as observed in keratinocytes [35,39], and actually lead to increased hyaluronan production.…”
Section: Receptors and Signals Of Extracellular Adenine Nucleotides -mentioning
confidence: 99%